Trends over time and risk factors in inappropriate prescribing in older adults with multimorbidity and polypharmacy: a longitudinal secondary analysis of the OPERAM trial (Swiss Medical Weekly, 2026)
BACKGROUND AND AIM OF THE STUDY: Polypharmacy is common among older adults and associated with potentially inappropriate medications and potential prescribing omissions, which together constitute potentially inappropriate prescriptions, contributing to adverse outcomes and increased healthcare costs. Longitudinal data on potentially inappropriate prescriptions and differences across living environments are limited. Our aim was to analyse patterns and determinants of potentially inappropriate prescriptions in multimorbid, older adults across different living environments and their trends over 12 months.METHODS: We used data from the control group (n = 1045) of the multi-country OPERAM trial (December 2015 – October 2018), a cluster-randomised controlled trial including older adults aged ≥70 years with ≥3 chronic conditions and ≥5 medications, which tested a software intervention to improve prescribing in these patients. The control group received pharmaceutical care in accordance with usual care. STOPP/START criteria were applied to detect potentially inappropriate prescriptions at hospital admission, discharge, and at 2-, 6- and 12-month follow-up. The outcomes were a priori defined as the prevalence of potentially inappropriate prescriptions at hospital admission, differences in potentially inappropriate prescriptions between living settings (nursing home versus community-dwelling) and number of medications (polypharmacy [5–9 medications] versus hyperpolypharmacy [≥10 medications]), changes in potentially inappropriate prescriptions over the 12-month follow-up and factors associated with potentially inappropriate prescriptions. Analyses included descriptive statistics and multivariable regression.RESULTS: At admission, 664 (63.5%) patients had ≥1 potentially inappropriate medication and 754 (72.1%) had ≥1 potential prescribing omission. Potentially inappropriate prescriptions at admission were most strongly associated with hyperpolypharmacy (potentially inappropriate medication: incidence rate ratio [IRR] 1.54, 95% CI 1.35–1.76) and cognitive impairment (potentially inappropriate medication: IRR 1.44, 95% CI 1.16–1.79), and were also significantly associated with female sex, number of comorbidities, fall history, nursing home residency and older age. Although overall prevalence remained stable over 12 months, substantial individual-level changes occurred, with many patients experiencing increases or decreases in the number of potentially inappropriate medications or potential prescribing omissions, alongside notable shifts in specific potentially inappropriate medications/potential prescribing omissions. An increasing number of potentially inappropriate prescriptions over time was mostly associated with hyperpolypharmacy (potential prescribing omission: OR 1.71, 95% CI 1.20–2.42 at 12 months) and nursing home residency (potentially inappropriate medication: OR 1.94, 95% CI 1.12–3.36 at 12 months), while significant associations were found for fall history and number of comorbidities.CONCLUSION: Potentially inappropriate prescriptions remain highly prevalent in multimorbid, older adults and do not clearly improve over time. Frequent changes at patient level and dynamic shifts in specific potentially inappropriate medications/potential prescribing omissions over time underscore the need for individualised, continuous medication reviews addressing both over- and underprescribing. Factors associated with increasing potentially inappropriate prescriptions over time may serve as indicators of high-risk patients and highlight the need for targeted interventions and further research.Study registration: This study is based on data from the OPERAM trial, which was registered at ClinicalTrials.gov (NCT02986425).